PENGARUH HARGA DAN KEPERCAYAAN TERHADAP NIAT PEMBELIAN ONLINE DENGAN PERSEPSI NILAI SEBAGAI VARIABEL MEDIASI (Studi Pada Konsumen Blibli.com di Kota Banda Aceh) - Khairul Amal, Hafasnuddin (Departemen Manajemen, 2017)
This study aims to determine the effect of the trust and the price of the purchase intention with the perceived value as mediating variable. Sampling technique used is purposive sampling, with a sample of 100 people in the city of Banda Aceh .Teknik analytical in this study using a model HLM (A hierarchical linear model). The results showed that the confidence and bepengaruh significantly influence purchase intention, confidence and significant effect on the perception of value, perceived value significantly influence purchase intentions, beliefs significantly influence purchase intention through perceived value as mediating variable prices and significant effect on the perception of value through perception of value as mediation. The implications of online stores blibli.com in this study need to increase confidence and to increase purchase intention mediated by perceived valueKeyword : Trust, Price, Perceived Value, Purchase Intentions.